PENGARUH PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT BERBANTUAN EDUCAPLAY TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII SMP NEGERI 1 SELEMADEG TIMUR - Ni Luh Putu Ayu Intan Suarningsih; Ni Nyoman Parwati; I Nengah Suparta (Penerbit Widina, Widina Media Utama, 2026)
Mastery of mathematical concepts occupies a strategic position in the learning process, as it serves as the foundation for students' reasoning and problem-solving abilities. However, the reality of learning shows that this achievement is not optimal, as evidenced by the tendency of students to rely on procedural memorization without adequate conceptual understanding. This condition demands the implementation of an instructional approach that can activate students' role in constructing knowledge. This study aims to analyze the effect of the Teams Games Tournament (TGT) learning model combined with Educaplay media on the mathematical concept comprehension abilities of seventh-grade students of SMP Negeri 1 Selemadeg Timur. This study uses a quasi-experimental approach with a Post-test Only Control Group Design. All seventh-grade students of SMP Negeri 1 Selemadeg Timur in the current academic year, totaling 89 students and spread across three classes, were designated as the study population. Sample selection was carried out using a cluster random sampling technique, resulting in two classes as samples, each consisting of 32 students. The experimental group received learning with the TGT model assisted by Educaplay, while the control group received direct learning. Data were collected using a mathematical concept understanding test instrument that met the criteria for validity and reliability. Data processing was performed using a t-test (independent samples test) at a 5% significance level. The results of the descriptive analysis showed that the average score for mathematical concept understanding in the experimental group reached 87.91, while the control group obtained an average score of 81.41. Hypothesis testing resulted in a significance value of 0.007, which is below the 0.05 limit. These findings indicate a significant difference between the two groups. Thus, it can be concluded that the implementation of the Teams Games Tournament learning model supported by Educaplay media has a significant influence on improving students' mathematical concept understanding abilities.ABSTRAKPenguasaan konsep matematika menempati posisi strategis dalam proses pembelajaran, karena menjadi landasan bagi kemampuan bernalar dan pemecahan masalah siswa. Akan tetapi, realitas pembelajaran menunjukkan bahwa capaian tersebut belum optimal, yang tampak dari kecenderungan peserta didik mengandalkan hafalan prosedural tanpa disertai pemaknaan konseptual yang memadai. Kondisi ini menuntut penerapan pendekatan instruksional yang mampu mengaktifkan peran siswa dalam membangun pengetahuan. Penelitian ini diarahkan untuk menganalisis pengaruh penerapan model pembelajaran Teams Games Tournament (TGT) yang dipadukan dengan media Educaplay terhadap kemampuan pemahaman konsep matematika siswa kelas VII SMP Negeri 1 Selemadeg Timur. Studi ini menggunakan pendekatan kuasi-eksperimen dengan rancangan Post-test Only Control Group Design. Seluruh siswa kelas VII SMP Negeri 1 Selemadeg Timur pada tahun ajaran berjalan, yang berjumlah 89 siswa dan tersebar dalam tiga kelas, ditetapkan sebagai populasi penelitian. Pemilihan sampel dilakukan melalui teknik cluster random sampling, sehingga diperoleh dua kelas sebagai sampel, masing-masing terdiri atas 32 siswa. Kelompok eksperimen memperoleh pembelajaran dengan model TGT berbantuan Educaplay, sedangkan kelompok kontrol mengikuti pembelajaran langsung. Data dikumpulkan menggunakan instrumen tes pemahaman konsep matematika yang telah memenuhi kriteria validitas dan reliabilitas. Pengolahan data dilakukan melalui uji t (independent samples test) pada taraf signifikansi 5%. Hasil analisis deskriptif menunjukkan bahwa rerata skor pemahaman konsep matematika pada kelompok eksperimen mencapai 87,91, sementara kelompok kontrol memperoleh nilai rata-rata sebesar 81,41. Pengujian hipotesis menghasilkan nilai signifikansi sebesar 0,007 yang berada di bawah batas 0,05. Temuan tersebut mengindikasikan adanya perbedaan yang bermakna antara kedua kelompok. Dengan demikian, dapat disimpulkan bahwa penerapan model pembelajaran Teams Games Tournament yang didukung oleh media Educaplay memberikan pengaruh signifikan terhadap peningkatan kemampuan pemahaman konsep matematika siswa.